1980
DOI: 10.1136/bmj.281.6234.189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pseudoephedrine and triprolidine, alone and in combination, on symptoms of the common cold.

Abstract: Summary and conclusions A total of 466 healthy adults from four different regions of England entered a double-blind, randomised trial to test the effectiveness of an antihistamine (triprolidine) and a decongestant (pseudoephedrine), alone or in combination, in relieving symptoms of the common cold. During the study 199 subjects reported a total of 243 colds. Subjects recorded the severity of 12 symptoms during treatment and noted separately the severity of a further seven symptoms that represented unwanted eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…Specifically, pseudoephedrine was found to reduce subjective or objective measures of congestion3, 8, 10, 16 but has little effect on sneezing,8 on pain10 or on non‐congestion cold symptoms in general 3. In the present survey, the ibuprofen/pseudoephedrine combination product differentially affected the extent of intra‐individual improvement of specific symptoms.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Specifically, pseudoephedrine was found to reduce subjective or objective measures of congestion3, 8, 10, 16 but has little effect on sneezing,8 on pain10 or on non‐congestion cold symptoms in general 3. In the present survey, the ibuprofen/pseudoephedrine combination product differentially affected the extent of intra‐individual improvement of specific symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…To reflect real‐world conditions a patient survey was performed, which excludes a placebo group. This was not deemed necessary as the efficacy of ibuprofen,6 pseudoephedrine3, 6, 7, 8, 10, 14, 15, 16, 17, 18 or their combination6, 7 in the treatment of common cold symptoms has been established in multiple placebo‐controlled studies. Moreover, common cold sufferers had correctly identified whether they were on active treatment or placebo in previous studies,8 questioning the value of a placebo group in this indication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent controlled trials with alkylamine-type antihistamines (e.g., chlorpheniramine and triprolidine) have reported reductions in certain symptoms of natural colds (12,19,56). One multicenter study (56) of oral chlorpheniramine reported statistically significant but modest (generally <10 to 15%) reductions in symptoms of nasal discharge, sneezing, and nose blowing, compared with placebo.…”
Section: Symptomatic Therapymentioning
confidence: 99%
“…Combinations of pseudoephedrine and an antihistamine have also been recommended to give relief of the symptoms of the common cold. Their value there is difficult to prove but in one randomized, placebo-controlled, double-blind study, Bye et al (28) were able to show in a large number of subjects (466 healthy adults) that sneezing, nasal obstruction and overall response to treatment were significantly improved by pseudoephedrine or pseudoephedrine and triprolidine combined compared with placebo or triprolidine alone.…”
Section: Other C O N D I T I O N Smentioning
confidence: 99%